Modeling and simulation in process hazard analyses - Azevedo, Júlia Pinto Athanázio de (2019)
The present work aims to develop a systematic way to use computational simulations for hazard identification, in order to tackle drawbacks related to the traditional methods, and proposes a methodology that is based on the association of the main points of previous works, with new contributions regarding the preparation for the simulations and the characterization of the minimum set of process variables that can enable appropriate interpretation of the results. In order to illustrate the proposed procedure, the propene polymerization process (LIPP-SHAC process) was used as a case study. As a result, hazard analyses based on modeling and simulation - complemented by a frequency study based on the Monte Carlo method - was compared to an independent traditional HAZOP study, in order to highlight the main differences and advantages of each method. Besides, additional modeling aspects were evaluated with the help of simulation performed with different models, in order to investigate the effects of model assumptions and parameter values when the model is used in a wide range of operating conditions. Finally, recommendations for use of models and simulations for hazard identification are proposed, aiming to encourage the use of these tools for risk analysis.